Construct Equivalence and Latent Means Analysis of Health Behaviors Between Male and Female Middle School Students - Jeong Mo Park, RN, PhD; Ae Kyung Han, RN, PhD; Yoon Hee Cho, RN, PhD (Elsevier, 2011)
Purpose: The purpose of this study was to investigate the construct equivalence of the five general factors (subjective health, eating habits, physical activities, sedentary lifestyle, and sleeping behaviors) and to compare the latent means between male and female middle school students in Incheon, Korea. Methods: The 2008 Korean Youth Risk Behavior Survey data was used for analysis. Multigroup confirmatory factor analysis was performed to test whether the scale has configural, metric, and scalar invariance across gender. Results: Configural invariance, metric invariance, and factor invariance were satisfied for latent means analysis (LMA) between genders. Male and female students were significantly different in LMA of all factors. Male students reported better subjective health, consumed more fast food and carbonated drinks, participated in more physical activities, showed less sedentary behavior, and enjoyed better quality of sleep than female students. Conclusion: Health providers should consider gender differences when they develop and deliver health promotion programs aimed at adolescents.